Hubungan Antara Gangguan Depresi dengan Kualitas Hidup, Stresor Psikososial, dan Tingkat Kontrol Asma pada Pasien Asma di RSUPN Dr. Cipto Mangunkusumo - Putro, Agung W; Kusumadewi, Irmia; Rengganis, Iris; Agiananda, Feranindhya (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2018)
Introduction : Poor asthma control level and the presence of comorbid disorders such as depression and psychosocial stress will affect the quality of life and increase the economic burden of asthmatic patients and their family. We investigated the correlation between depressive disorders, quality of life, psychosocial stressors, and level of asthma control in asthmatic patients. Methods : The study was cross-sectional descriptive-analytic in 37 asthmatic patients with depressive disorder and 37 asthmatic patients without depressive disorder in the Allergy and Immunology Clinic RSUPN Dr. Cipto Mangunkusumo using SCID-1, WHOQOL-BREF, Holmes and Rahepsychosocial stressors, and ACT questionnaires. Results : There is a relation between the presence of depressive disorders and lower quality of life scores based on physical health (p less-than 0,001), psychological health (p less than 0,001), social relations (p=0.023), environment (p=0.022), psychosocial stressors (OR 3.85; p=0.005), and the level of asthma control (p=0.001) in asthmatic patients. Conclusion: Asthmatic patients with depressive disorders tend to have lower quality of life score in all domains (physical health, psychological health, social relationships, and environment) and lower level of asthma control scores than asthmatic patients without depressive disorders. Asthmatic patients who have psychosocial stressors have 3.8 times higher risk to have depressive disorders.